Rare earth element partitioning between sulphides and melt: Evidence for Yb2+ and Sm2+ in EH chondrites. (15th November 2019) - Ingrao, N.J.; Hammouda, T.; Boyet, M.; Gaborieau, M.; Moine, B.N.; Vlastelic, I.; Bouhifd, M.A.; Devidal, J.-L.; Mathon, O.; Testemale, D.; Hazemann, J.-L.; Proux, O.
Abstract: We present the first complete dataset of partition coefficients of Rare Earth Elements (REE) between oldhamites or molten FeS and silicate melts. Values have been determined at 1300 and 1400 °C from experiments on mixtures of a natural enstatite chondrite and sulphides powders (FeS or CaS) performed in evacuated silica tubes for different f O 2 conditions (from IW-6.9 to IW-4.1). Obtained REE partitioning values are between 0.5 and 5 for oldhamites and between 0.001 and 1 for FeS. In both sulphides, Eu and Yb are preferentially incorporated compared to neighbouring REE. X-ray Absorption Near Edge Structure measurements on Yb and Sm demonstrate the partial reduction to 2+ valence state for both elements, Yb reduction being more pronounced. Therefore, the Yb anomaly in the sulphides is interpreted to be an effect of the presence of Yb 2+ in the system and the amplitude of the anomaly increases with decreasing oxygen fugacity. The obtained oldhamite/silicate melt partition coefficients patterns are unlike any of the observed data in natural oldhamites from enstatite chondrites and achondrites. In particular, the low values do not explain the observed enrichments in oldhamite crystals. However, positive Eu and Yb anomalies are observed in some oldhamites from EH chondrites and aubrites. We attribute these anomalies found in meteorites to the sole oldhamite control on REE budget. We conclude that the presence of positive Eu and Yb anomalies in oldhamites is a good indicator of their primordial character and that these oldhamites carry a condensation signature from a highly reduced nebular gas.